2023
DOI: 10.3390/microorganisms11071784
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Psidium guajava Aqueous Extract against Sensitive and Resistant Bacterial Strains

Abstract: The inappropriate use of antimicrobials, along with environmental conditions, can lead to the emergence of resistant microorganisms. The use of phytopharmaceuticals and herbal medicines has a positive impact and represents a promising alternative. Psidium guajava extracts have been widely reported to have antimicrobial potential; however, studies reporting their activity against resistant bacterial strains are scarce. Because of the emerging resistance, the aim of this study was to analyze the antimicrobial ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…Previously, the antibacterial activity of the methanolic leaf extract of guava was reported with the mean zone of inhibition ranging from 8.27 ± 0.44 to 12.3 ± 0.78 mm [4] whereas in the present study, the mean zone of inhibition ranged from 17.67 ± 0.57 to 25.66 ± 0.57 mm which is comparatively higher than the previous reports. To support our study, Pereira et al [49] reported that the methanolic leaf extract of P. guajava had greater antibacterial activity against Gram-positive and Gram-negative bacterial strains and recorded the highest zone of inhibition with 21.0 ± 2.0 mg/mL against the bacterial strain Streptococcus beta-hemolytic. Previously, the antibacterial activity of the methanolic leaf extract of guava was reported with the mean zone of inhibition ranging from 8.27 ± 0.44 to 12.3 ± 0.78 mm [4] whereas in the present study, the mean zone of inhibition ranged from 17.67 ± 0.57 to 25.66 ± 0.57 mm which is comparatively higher than the previous reports.…”
Section: Antibacterial Activity Of Guava Leaf Cultivarssupporting
confidence: 87%
See 2 more Smart Citations
“…Previously, the antibacterial activity of the methanolic leaf extract of guava was reported with the mean zone of inhibition ranging from 8.27 ± 0.44 to 12.3 ± 0.78 mm [4] whereas in the present study, the mean zone of inhibition ranged from 17.67 ± 0.57 to 25.66 ± 0.57 mm which is comparatively higher than the previous reports. To support our study, Pereira et al [49] reported that the methanolic leaf extract of P. guajava had greater antibacterial activity against Gram-positive and Gram-negative bacterial strains and recorded the highest zone of inhibition with 21.0 ± 2.0 mg/mL against the bacterial strain Streptococcus beta-hemolytic. Previously, the antibacterial activity of the methanolic leaf extract of guava was reported with the mean zone of inhibition ranging from 8.27 ± 0.44 to 12.3 ± 0.78 mm [4] whereas in the present study, the mean zone of inhibition ranged from 17.67 ± 0.57 to 25.66 ± 0.57 mm which is comparatively higher than the previous reports.…”
Section: Antibacterial Activity Of Guava Leaf Cultivarssupporting
confidence: 87%
“…Previously, the antibacterial activity of the methanolic leaf extract of guava was reported with the mean zone of inhibition ranging from 8.27 ± 0.44 to 12.3 ± 0.78 mm [4] whereas in the present study, the mean zone of inhibition ranged from 17.67 ± 0.57 to 25.66 ± 0.57 mm which is comparatively higher than the previous reports. To support our study, Pereira et al [49] reported that the methanolic leaf extract of P. guajava had greater antibacterial activity against Gram-positive and Gram-negative bacterial strains and recorded the highest zone of inhibition with 21.0 ± 2.0 mg/mL against the bacterial strain Streptococcus beta-hemolytic.…”
Section: Antibacterial Activity Of Guava Leaf Cultivarssupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, it is perceived to be effective in hematopoiesis through increasing the number of red blood cells and bone marrow erythroid cells. Examining the antioxidant activity of guava hydroalcoholic extract shows that this extract plays a great role in trapping free radicals and preventing anemia [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that, since guava leaf hydroalcoholic extract is rife with flavonoids, tannins, ellagic acid, triterpenes and quercetin, it can provide favorable conditions for the growth and differentiation of stem cells into hematopoietic cells and help in the regeneration of blood tissue. These compounds can protect cell membranes, including red blood cell membranes, from damage caused by free radicals, prevent their destruction, and hence increase their count in the blood [30][31][32].…”
Section: Discussionmentioning
confidence: 99%